(untitled) (Global Journal of Human-Social Science, 2021)
The aim of this work is to point out and describe Terminology problems related to the diachronic variation of a terminology based on the conceptual analysis1of two structures, concerning two process models (sugar plantation and factory) of a same technical area -sugar production, separated by a certain period of time and submitted to constant technological, linguistic and cultural revolutions. For this reason, we described the factors, which interfere in those transformations; the manner that the consolidation level of a social sphere represents its systemic regularity; and we tried to prove, based on a diachronic research, that the dynamics of the speciality subsystems has the same functioning of the one that rules the general language.